HiCare: Aplikasi Pengaduan Kekerasan Seksual berbasis Mobile - Muhammad Rifqi Zaki Rizqullah; Wahyu Sri Utami (Universitas Hamzanwadi, 2023)
The rise of sexual violence on campus has a traumatic impact on victims, so there is a need for a special platform that functions as a medium for reporting sexual violence. This research aims to build a sexual violence complaint application called HiCare for Android and iOS. The method used in developing this software is the Software Development Life Cycle (SDLC) with several stages, planning is carried out for system planning. system analysis is carried out by directly reviewing the running system and data collection is carried out through interviews and observations, system design to design use cases, activity diagrams and user interface design, implementation using Flutter in the implementation process, and testing with black box testing to test system suitability. The result of our findings is a mobile-based sexual violence complaint application called HiCare. The application can run well on the Android and iOS operating systems, as proven by black box testing.